2012
DOI: 10.1016/j.ijid.2012.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low bone mineral density in a Brazilian cohort of vertically HIV-infected adolescents

Abstract: Control of the HIV infection, especially before the initiation of puberty, might have a positive influence on bone gain. Body composition and nutritional status had a positive influence on BMD that was more evident in females, suggesting that nutritional intervention may have a positive impact on BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 37 publications
4
60
2
Order By: Relevance
“…Most studies were conducted in high income countries, including the United States [6, 7, 2132], Italy [3344], Canada [45], and the Netherlands [46]. Three studies were reported from middle-income countries, including one from Thailand [47] and two from Brazil [48, 49]. One study was conducted in three countries: the United States, Brazil, and Panama [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were conducted in high income countries, including the United States [6, 7, 2132], Italy [3344], Canada [45], and the Netherlands [46]. Three studies were reported from middle-income countries, including one from Thailand [47] and two from Brazil [48, 49]. One study was conducted in three countries: the United States, Brazil, and Panama [50].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies enrolled children known to be HIV-uninfected but exposed to HIV in utero as a control group [29, 30] and one study recruited HIV-uninfected siblings [24]. Other studies drew comparisons with a number of existing cross-sectional or longitudinal normative databases comprised of healthy children from single or multiple study sites [2123, 2628, 34, 45, 47] or provided by the densitometer manufacturer [24, 41, 43, 46, 48, 49]. Bone densitometry by DXA was the predominant method for evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…In cross-sectional studies to assess bone mineral density among perinatally HIV-infected children and adolescents receiving ART, the reported prevalence rate of BMD z-score <−2 is in a range of 24-32%. [69][70][71][72] Longitudinal assessment of BMD show that the median BMD z-scores usually decline from baseline in the first 6-12 months after initiation of ART and then remain stable thereafter. 65,73 This is similar to reports from HIVinfected adults that the decrease in BMD was seen early during the first 48 weeks of therapy, and then stable up to 5 years of follow-up.…”
Section: Tdf Effect On Bone Mineral Densitymentioning
confidence: 99%
“…For example, the Brazilian study reported low calcium and vitamin D intake in 72.9% and 91.5% of HIV-infected children, respectively. 72 In summary, the adverse impact of TDF on bone is well documented but its clinical significance remains controversial. More long-term studies are needed to see whether any clinically significant events occur.…”
Section: Tdf Effect On Bone Mineral Densitymentioning
confidence: 99%
“…It is noteworthy that TDF is not unique in its ability to cause a reduction in BMD. HIV infection itself and many other antiretroviral drugs also cause a decline in BMD [51][52][53][54][55]. Vitamin D deficiency is common in children with HIV infection, and this may be an additional factor in the development of bone disease; supplementation may be required in some cases [40].…”
Section: Discussionmentioning
confidence: 99%